2020
DOI: 10.15517/rbt.v68i4.41218
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the entomopathogenic fungus Beauveria bassiana as an endophyte in Capsicum annuum and its effects on the aphid pest Myzus persicae (Homoptera: Aphididae)

Abstract: Introduction: Entomopathogenic fungi have been used as biological control agents of insect pests and have demonstrated a promising ability to colonize as endophytes a wide range of plant species. Objective: The aims of this study were to evaluate, in pepper plants, the most effective Beauveria bassiana inoculation techniques. In order to evaluate the presence of natural endophytes and its interaction with B. bassiana. Also to assess the effect of B. bassiana on the aphid Myzus persicae pepper leaf feeding pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…These studies provided evidence that B. bassiana was also indirectly effective against aphids via endophytism. Even if Allegrucci et al [81] did not find significant aphid mortality differences on pepper (Capsicum annuum L.) endophytically colonized by B. bassiana and control plants, aphids more numerously died on B. bassiana-inoculated plants. Such an increased mortality in aphids settled on endophytically colonized plants was previously attributed to a possible improvement in plant resistance conferred by EEPF [27,95].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These studies provided evidence that B. bassiana was also indirectly effective against aphids via endophytism. Even if Allegrucci et al [81] did not find significant aphid mortality differences on pepper (Capsicum annuum L.) endophytically colonized by B. bassiana and control plants, aphids more numerously died on B. bassiana-inoculated plants. Such an increased mortality in aphids settled on endophytically colonized plants was previously attributed to a possible improvement in plant resistance conferred by EEPF [27,95].…”
Section: Discussionmentioning
confidence: 93%
“…The effectiveness of B. bassiana as a biological control agent against phloem-feeding insects and especially aphids are well-known and widely documented [21,26,28,30,[80][81][82][83][84][85][86]. The most common treatment method use in the field and in the laboratory is the direct contact between the EPF spores and the insect pest [87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los daños que ocasionan los pulgones, mosca blanca y ácaros en el pimiento se deben al tipo de aparato bucal que poseen, tienen la capacidad de succionar la sabia de hojas, f lores y frutos; producen manchas cloróticas, manchas oscuras o rojas, amarillamiento, abscisión prematura de las hojas infestadas, estrés hídrico; marchitamiento, reducción del crecimiento, maduración irregular del fruto, por lo que, la calidad y el rendimiento de los cultivos es afectado (Xue, Wang, Bi, Li y Liu, 2010;Mao y Zeng, 2013;Fonte, Garcerá, Tena y Chueca, 2019). Adicionalmente, muchas especies de las antes mencionadas son consideradas importantes vectores de virus en el cultivo de pimiento y otras hortalizas (Castresana y Puhl, 2018;Allegrucci et al, 2020;Fortes, Fernández y Moriones, 2020).…”
Section: Introductionunclassified
“…Recently, some publications have shown that the establishment of B. bassiana as an endophyte in pepper improved several plant growth parameters and had a controlling effect against the insect pest Myzus persicae (Hemiptera: Aphididae) and the fungal disease caused by Botrytis cinerea Pers. (Helotiales: Sclerotiniaceae) (Jaber and Araj 2018;Allegrucci et al 2020;Barra-Bucarei et al 2020).…”
Section: Introductionmentioning
confidence: 99%